Literatura i jej twórcy w "Tygodniku Powszechnym" (2001-2005) - Wieczorek, Karolina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2008)
The article refers to presence of literature in catholic-advisor title Tygodnik Powszechny (years 2001-2005). Article is divided on parts: history, authors, literature texts (essays, reviews, lyric poetry). We find here analysis of literature texts, which was published in weekly magazine in years we are writing about and systematic of frequency in present sorts. Author looks for answers for questions: How many place take in Tygodnik articles of literature (we talking mostly about years 2001-2005)?, What sorts of literature and journalism are dominating in magazine?. Who writes for Tygodnik? The article gives all these answers and many other different questions. It sets modern literature texts with earlier situation of literature which was published in previous years.